Lysosomal stress and lipid peroxidation products induce VEGF-121 and VEGF-165 expression in ARPE-19 cells - Bergmann, Marion; Holz, Frank G.; Kopitz, Jürgen (Graefe's archive for clinical and experimental ophthalmology, 2011)
Pathologically increased VEGF-A expression is considered a major pathogenic factor in exudative AMD. Since VEGF-A can exist in isoforms with different individual functions, for a detailed understanding of the role of VEGF-A in normal and disease associated processes, in particular in wet AMD, the expression pattern of VEGF-A isoforms has to be taken into account. Therefore in the present study, adressing the effects of lysosomal dysfunction on VEGF expression and secretion by RPE cells induced by lipid peroxidation products and an inhibitor of lysosomal acidification, we applied quantitative methods discriminating the major VEGF-A isoforms.
Gesehen am 17.03.2022